The Distribution of Products - Hawley, Frederick B. (Quarterly Journal of Economics, 1888)
The Distribution of Products Get access Frederick B. Hawley Frederick B. Hawley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 3, Issue 1, October 1888, Page 109, https://doi.org/10.2307/1881859 Published: 01 October 1888